VO2peak Response Heterogeneity in Persons with Multiple Sclerosis: To HIIT or Not to HIIT? - Lea Schlagheck, Marit; Wucherer, Anika; Rademacher, Annette; Joisten, Niklas; Proschinger, Sebastian; Walzik, David; Bloch, Wilhelm; Kool, Jan; Gonzenbach, Roman; Bansi, Jens; Zimmer, Philipp (International Journal of Sports Medicine, 2021)
Exercise is described to provoke enhancements of cardiorespiratory fitness in persons with Multiple Sclerosis (pwMS). However, a high inter-individual variability in training responses has been observed. This analysis investigates response heterogeneity in cardiorespiratory fitness following high intensity interval (HIIT) and moderate continuous training (MCT) and analyzes potential predictors of cardiorespiratory training effects in pwMS. 131 pwMS performed HIIT or MCT 3–5x/ week on a cycle ergometer for three weeks. Individual responses were classified. Finally, a multiple linear regression was conducted to examine potential associations between changes of absolute peak oxygen consumption (absolute ∆V̇O2peak/kg), training modality and participant’s characteristics. Results show a time and interaction effect for ∆V̇O2peak/kg. Absolute changes of cardiorespiratory responses were larger and the non-response proportions smaller in HIIT vs. MCT. The model accounting for 8.6% of the variance of ∆V̇O2peak/kg suggests that HIIT, younger age and lower baseline fitness predict a higher absolute ∆V̇O2peak/kg following an exercise intervention. Thus, this work implements a novel approach that investigates potential determinants of cardiorespiratory response heterogeneity within a clinical setting and analyzes a remarkable bigger sample. Further predictors need to be identified to increase the knowledge about response heterogeneity, thereby supporting the development of individualized training recommendations for pwMS.
Keywords: cardiorespiratory fitness; exercise; high intensity interval training; moderate continuous training; multiple sclerosis; response heterogeneity